Reactivity of the Pyrimidine Nitrogen Atom toward an Acetal Moiety: Formation of 3-Ethoxy-2,3-dihydroimidazo[1,2-c]pyrimidines by Intramolecular Cyclization of N-(2,2-Diethoxyethyl)pyrimidine-4-amines - Juskenas, Robertas; Masevicius, Viktoras; Tumkevicius, Sigitas (Synthesis, 2013)
A new protocol was developed for the synthesis of 2,3-dihydroimidazo[1,2-c]pyrimidines, based on an intramolecular reaction between a pyrimidine nitrogen atom and an acetal moiety in the presence of boron trifluoride etherate. The method was expanded to permit the synthesis of the triheterocyclic imidazo[1,2-c]pyrazolo[4,3-e]pyrimidine system.
Keywords: acetals; cyclizations; heterocycles; polycycles; pyrimidines; imidazoles